Formative experience in monocultural schools in Araucanía, Chile: memories of women in Cholchol and Maquehue (2019)
This research is framed in the preliminary results of a regular Fondecyt project and its aim is to reveal and describe the social memory of five women who are indigenous grandmothers of the Mapuche communities in Maquehue and Cholchol areas. All of them aged between sixty and seventy years. Based on subjectivities, particularities, and feelings of the Mapuche grandmothers, main agents of intergenerational cultural transmission, the text addresses the problem of the invisibility of indigenous ancestral wisdom. The theoretical framework is based on the intercultural approach and, on the Mapuche formative model Kimeltuwun (Mapuche educational process) which is conveyed through epew (stories), peumas (dreams) and piam (ancient narratives). The stories were socialized in their own territories, just where they shared their school experiences; this factor, undoubtedly, enriched the research experience. The reconstruction of memory arises from the monocultural schooling they shared in their childhood. The data were collected through in-depth interviews and nuw tram, as part of an intercultural approach to the countryside. The results show how their ancestral knowledge became invisible in the education they received, overloaded with discipline and rigidity, and always focused on domestic roles (washing dishes, cleaning floors, looking for firewood), completely distant from their own recognition, identity, self-improvement and social participation, their ancestral legacy and their context was left aside. The school invades its culture, ignores it, moves them away from their Mapuche essence, which consists essentially of a life in harmony with nature.